Modes of discourse : the local structure of texts - Smith, Carlota S. (Cambridge studies in linguistics, 2003)
In studying discourse, the problem for the linguist is to find a fruitful level of analysis. Carlota Smith offers a new approach with this study of discourse passages. She introduces the key idea of the 'Discourse Mode', identifying five modes and analyzing the properties that distinguish each mode.